Gender, Language and Indian Reality Television: Locating Social Stereotypes and Linguistic Sexism - Alam, Sohaib; Haque, Shafey Anwarul (Journal of Education Culture and Society, 2021)
Aim. The reality genre has gained much popularity in last few years across the globe. In India too, this genre has reportedly surpassed other genres in recognition and acceptance. However, its format and content intrigue controversies at both social and academic level, but its mass appeal gets bigger each day. The study examines gender, language and issues of gendered language in Indian reality show Bigg Boss. While keeping in view the format and claim of the genre, the study observes how under thorough surveillance, housemates negotiate with their real self and grapple with their language practice. Influence of neoliberalism on society, culture and identity has been very much discussed, the paper attempts to highlight how this transitions in gender identity is depicted in a show taking non-actors and common people. Concept. For the purpose of the study, scripted transcription of Bigg Boss (Season 11) has been used, wherein all the episodes of have been watched back and forth carefully, and detailed notes prepared for the analysis. Housemates’ language practice, voice pattern and preference of words and statements have been observed. Results and conclusion. The study finds that game reality show Bigg Boss substantially adheres to social stereotypes and standards and while doing so, it also imitates the language practice prevalent everywhere. Although active participation of women in the show is visible butt while exhibiting their true self, sometimes gender prejudice embedded deep inside also comes out, which in case of men is very frequent. The study concludes that as a globally acclaimed genre, reality show, like other genres, is very much commercialized and consumer oriented. Originality. A number of studies related to reality shows have been conducted, but in Indian context, this genre has been inadequately explored. Also, it is very difficult to find studies focusing any specific season of an Indian reality show, so it would not be incorrect to mention that the present study is one of the primary works on this subject, which aims at making some significant contribution related to this genre, in academia.